Les graphes pour étudier les dynamiques spatiales à partir des séries fiscales médiévales et modernes. Etat des lieux de l’expérience Modelespace - Samuel Leturcq; Romain Raveaux (Bulletin du Centre d’Études Médiévales d’Auxerre)
From 2010 till 2012, the Modelespace program introduced a research to work out a methodology to analyse the spatial dynamics by leaving of the comparison between different sets of spatial data of fiscal documents of medieval and modern periods (fieldbooks and land registry, called cadastres, catasti, compoix, estimes… in southern Europe) with the graph theory. We explain the significant advances of the methodology, and we propose different ways to establish the comparison method of the graphs.